2019
DOI: 10.1039/c9qo00037b
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular crowns: a new class of cyclic hydrogen-bonded cavitands

Abstract: A novel design of highly preorganized bicyclic monomers, based on quadruple hydrogen bonding motifs, is proposed to access noncovalent cavitands with large internal volumes and interesting shapes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The enantiopure bicyclo[3.3.1]­nonane scaffold appended with two H-bonding units at each end was selected as the working unit based on the previous successful utilization of similar compounds in creating extremely stable square-shaped or tubular cavity aggregates. The nearly 90° angle between the complementary ends renders these monomers highly preorganized for tetrameric cyclic aggregation. Moreover, their chirality-assisted aggregation provides full control over the formation of cavity aggregates and excludes the competing formation of unwanted zig-zag type H-bonded polymers.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enantiopure bicyclo[3.3.1]­nonane scaffold appended with two H-bonding units at each end was selected as the working unit based on the previous successful utilization of similar compounds in creating extremely stable square-shaped or tubular cavity aggregates. The nearly 90° angle between the complementary ends renders these monomers highly preorganized for tetrameric cyclic aggregation. Moreover, their chirality-assisted aggregation provides full control over the formation of cavity aggregates and excludes the competing formation of unwanted zig-zag type H-bonded polymers.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In the simplest hypothetical strategy towards a supramolecular tweezer, the C 2 -symmetric derivative UPy - UPy can be envisioned as a suitable building block (Figure a). It has been previously shown that UPy - UPy monomers of this type form stable tetrameric aggregates in a variety of solvents via quadruple H-bonding. , In order to form a tweezer aggregate, the monotopic UPy 1 derivative would be required as a partner. However, such an approach will potentially suffer from a serious drawback of having two competing monomers of the same strength (herein, we use the term “order” to define the multiplicity of the H-bonding array), whereas the cyclic aggregate formed by the ditopic monomer would be strongly reinforced by a chelation effect.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As another feature, the encapsulation that could be observed in toluene, but not in CHCl3, hindered scrambling between the two types of monomers 72a and 72b. In contrast to these compounds with the bicyclo[3.3.1]nonane framework, only the tetramer of the dioxabicyclo[3.3.1]nonane derivative 73 was observed, either in CHCl3 or in benzene [89]. Reversible formation of dimeric capsules from other star shaped molecules ( 71) was used for the purification of fullerenes that could be encapsulated in the cavity [87].…”
Section: Formation Of Different Molecular Architectures Via Supramole...mentioning
confidence: 99%
“…3.1]nonane central blocks, to create chiral cavities with tuneable stability, size and function. [111][112][113][114][115] For instance, bis-UPy molecule 13 112 allowed the formation of a cyclic tetramer by quadruple H-bonding interactions between monomers (Fig. 11a).…”
Section: Template Effectsmentioning
confidence: 99%